Attitudes of Portuguese Judges and Victim Support Professionals Toward Intimate Partner Homicide Committed by Women - Ferreira, Mafalda (2022)
This investigation analyzed the attitudes of Portuguese judges and victim support professionals toward intimate partner homicide committed by women. By administering an online survey disseminated by the Portuguese Superior Council for the Magistracy and the Commission for Citizenship and Gender Equality, we found that both groups of professionals are not always aligned in their attitudes toward domestic violence and intimate partner homicide, which could jeopardize the articulation between both sectors needed for an effective preventive intervention. However, most professionals of both groups tend to disagree that women provoke their aggressors or lie about their condition as victims of domestic violence and agree that there is a need for increased security and prevention of intimate partner homicides against female and male victims when reporting domestic violence.